Children Involvement in Artisanal Fishing: A Case Study of Lagos Lagoon, Nigeria - O. S, Fakayode; O. A, Adeogun; L. R, Unah; D. A, Bolaji (Asian Journal of Agriculture and Rural Development, 2016)
Children involvement in artisanal fishing was investigated between 2013 and 2014 to assess the percentage number of children involved in fishing on Lagos Lagoon, their roles, contribution and the effects of the activities on their livelihood. Structured and unstructured questionnaires were conducted by the researchers. Data collected were collated and analyzed using frequency distribution and percentages. The average number of boats fishing was 70 boats while average number of people counted was 168 and 55% were children between 3 – 17 years. During the study, we recorded a female which accounted for 0.2% while male was 99.8%, 6% of which were going to school and the roles played were paddling, operating engine, bailing water, sorting fish, casting net, setting gear. Enforcing law on the fisher folks to stop involving their children may jeopardize the effort of government on fish production, therefore the best way to reduce child labour in artisanal fishing is that government should intensify the right support in terms of aids and infrastructures to fisher folks on the ways of improving fishing methods for sustainable management of the fishery to support their children education.